2023
DOI: 10.1126/sciadv.adf7714
|View full text |Cite
|
Sign up to set email alerts
|

FERONIA and wall-associated kinases coordinate defense induced by lignin modification in plant cell walls

Abstract: Altering the content or composition of the cell wall polymer lignin is a favored approach to valorize lignin toward biomaterial and chemical production in the biorefinery. However, modifying lignin or cellulose in transgenic plants can induce expression of defense responses and negatively affect growth. Through genetic screening for suppressors of defense gene induction in the low lignin ccr1-3 mutant of Arabidopsis thaliana , we found that loss of function of th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
17
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 39 publications
(18 citation statements)
references
References 58 publications
1
17
0
Order By: Relevance
“…FER is the most extensively studied member of the malectin domain-containing receptor-like kinase (MLD-RLK) (also known as Catharanthus roseus RLK1-LIKE or CrRLK1L) family. It plays broad and profound roles in diverse processes including sexual reproduction, development of root hair, hormonal responses, mechanic sensing, plant-microbe interactions, and maintaining CWI under abiotic stresses (15)(16)(17)(18)(19)(20)(21)(22)(23)(24). Previous studies have shown that BR increases FER RNA level (12).…”
Section: Br Promotes Fer Accumulation At the Plasma Membranementioning
confidence: 99%
“…FER is the most extensively studied member of the malectin domain-containing receptor-like kinase (MLD-RLK) (also known as Catharanthus roseus RLK1-LIKE or CrRLK1L) family. It plays broad and profound roles in diverse processes including sexual reproduction, development of root hair, hormonal responses, mechanic sensing, plant-microbe interactions, and maintaining CWI under abiotic stresses (15)(16)(17)(18)(19)(20)(21)(22)(23)(24). Previous studies have shown that BR increases FER RNA level (12).…”
Section: Br Promotes Fer Accumulation At the Plasma Membranementioning
confidence: 99%
“…Our findings highlight the importance of the putative IDR in the extended C terminus of P2K1 in regulating eATP signaling, especially in the eATP-induced regulation of primary root growth. Additionally, our results suggest a critical role for eATP and P2K1 in regulating ROS and cell wall integrity in the primary root meristem, which are essential for plant growth and stress adaptation [57][58][59][60][61][62][63]. This study also provides a framework for generating other truncated RK variants based on IDRs that can help further unravel the functional significance of the C terminus in other receptor proteins.…”
Section: Discussionmentioning
confidence: 90%
“…Pectin is likely to be involved in cell wall loosening and remodeling, and PG, PL, and PE are plant hydrolytic enzymes that modulate the firmness or softening of cell walls through pectin disassembly (Atmodjo et al, 2013;Khan et al, 2019). The cell wall remodeling and the release of elicitor-active pectic polysaccharides are affected by FER receptor-like kinase (Liu et al, 2023). Duan et al (2020) demonstrated that FER is crucial for maintenance of de-esterified pectin.…”
Section: Discussionmentioning
confidence: 99%